Design of Negative Pressure Spiral Feeding Device for Tangential and Longitudinal Axial Intersection of Combine Harvester - Zhong Tang; Xiyao Li; Xinda Chen; Yang Chen (Advances in Materials Science and Engineering)
A difficult problem occurred with straw clogging at the tangential and longitudinal axial intersection of rice combine harvesters, which seriously affected the efficiency and reliability of the threshing cylinder. The primary objective of this paper was to design a negative pressure spiral feeding device by CFD (computational fluid dynamics). The negative pressure spiral feeding combined structure of the tangential threshing cylinder and longitudinal axial threshing cylinder was established by Pro/E software. Then, the flow path model of the negative pressure spiral feeding device was analyzed by CFD. The airflow velocity distribution of the spiral feed head semicircular cross section and power consumption of the longitudinal axial spiral feeding head were used to verify the effectiveness and rationality of the negative pressure spiral feeding device. The results showed that the two-blade spiral structure and 30 mm pitch shroud structure were more suitable to ensure the smooth flow of straw at the tangential and longitudinal axial intersection. The resistance of the feeding head would cause the power consumption curve fluctuation. The power consumption curve of the improved shroud spiral feed structure was a stable regular fold line without upward trend. When the power consumption curve has an always upward trend, it means that congestion is about to happen. The characteristics of the power consumption curve indicated that the shroud negative pressure spiral feed device designed in this paper was reasonable and effective.